Lifting-induced stability loss of vessels in shallow water. (1st June 2022) - Yu, Yaru; Johnson, Nick
Abstract: By incorporating several series of results from both experimental scale-model tests and URANS-based simulations, the transverse stability of a model (1:20) under lifting condition in shallow water is investigated and quantified. According to the results, a non-dimensionalised mass of 0.66 (% Δ ) on top of the lifting boom reduces GZ lever up to around 40% in calm water. In waves, the lifted object increases roll amplitude about 7–56% near roll natural frequency, and the smaller the waves, the larger the influence. Shallow water starts to have effects on roll, pitch, heave, and sway motions from a water depth/draught ratio of about 7 as opposed to 4 suggested by ITTC (2005). Maximum variations of those motion amplitudes are about 77%, 110%, 25%, and 500%, respectively. Double-peak-roll phenomenon appears to be both wave-frequency-dependant and water-depth-related, but at a depth/wavelength ratio of about 0.45 and above, motions are not affected. Highlights: Stability loss due to lifting operation in beam waves is investigated and quantified. Motion responses under lifting condition in shallow water are discussed. Double-peak-roll phenomenon is both wave-frequency-dependant and water-depth-related.